A Comparative Study of Efficacy and Safety of Oral Contraceptive Pills versus Intrauterine Devices in Preventing Unintended Pregnancy - Vishwanath Dange; V. Malathi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Unintended pregnancy remains a significant public health challenge worldwide, influencing the socio-economic and health outcomes for women. Oral Contraceptive Pills (OCPs) and Intrauterine Devices (IUDs) are widely used for contraception, but their comparative efficacy and safety have not been consistently evaluated across diverse populations. Objectives: This study aimed to compare the efficacy and safety of OCPs versus IUDs in preventing unintended pregnancies. Methods: A prospective observational cohort study was conducted involving 120 participants who were recruited from a family planning clinic and chose either OCPs or IUDs based on preference and medical suitability. The primary outcome measured was the rate of unintended pregnancies. Secondary outcomes included method continuation rates, user satisfaction, and the incidence of side effects. Data were analyzed using Chi-square tests, Fisher’s exact test, and Z-tests to compare proportions between the two groups. Results: The incidence of unintended pregnancies was significantly lower in the IUD group (1.7%) compared to the OCP group (6.7%), with a p-value of 0.037. Continuation rates were higher for IUD users (98.3%) than for OCP users (93.3%), with a significant difference (p-value = 0.045). The IUD group also reported fewer side effects and higher overall satisfaction. Safety profiles indicated fewer adverse effects among IUD users compared to those on OCPs. Conclusion: IUDs were found to be more effective and safer than OCPs in preventing unintended pregnancies. They also had higher user satisfaction and continuation rates. These findings support the use of IUDs as a preferable method of contraception for women seeking long-term prevention of unintended pregnancy. Limitations: The study’s limitations include its reliance on self-reported data, the non-randomized design, and the limited sample size and diversity which may affect the generalizability of the findings.